2016
DOI: 10.4103/1817-1737.191868
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic implications of computed tomography pulmonary angiography in patients with pulmonary embolism

Abstract: INTRODUCTION:Pulmonary embolism (PE) is a serious cardiovascular and pulmonary complication worldwide. We aimed to assess the implications of different computed tomography pulmonary angiography (CTPA) parameters in patients with acute PE.METHODS:A retrospective observational study to include patients presented with clinical suspicious of PE who underwent CTPA was conducted. Patients' demographics, clinical presentation, risk factors, laboratory investigations, management, and outcome were analyzed. Computed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
(70 reference statements)
0
12
0
3
Order By: Relevance
“…3 In the present study the proportion of males was slightly higher than females, which is consistent with an earlier study from our center and in the region. 26,27 Also, PE patients with thrombophilia were more likely to be younger and more frequently had a history of recurrent VTE than those without thrombophilia. Notably, there is a steep decline in the frequency of hereditary thrombophilia with age in our cohort, which is also evident from findings of the MAISTHRO registry suggesting that this could be attributed to the decrease in frequency of genetic defects and deficiency of PC or PS in individuals that developed an initial VTE event at an advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…3 In the present study the proportion of males was slightly higher than females, which is consistent with an earlier study from our center and in the region. 26,27 Also, PE patients with thrombophilia were more likely to be younger and more frequently had a history of recurrent VTE than those without thrombophilia. Notably, there is a steep decline in the frequency of hereditary thrombophilia with age in our cohort, which is also evident from findings of the MAISTHRO registry suggesting that this could be attributed to the decrease in frequency of genetic defects and deficiency of PC or PS in individuals that developed an initial VTE event at an advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…Emboli to the lungs cause physical obstruction of the pulmonary arteries yielding a pathophysiologic cascade resulting in varying degrees of cardiovascular distress[ 19 ]. Although the embolic load and distribution are considered less pertinent than the patient’s hemodynamic status in evaluating risk stratification[ 7 ] clot burden has been shown to have predictive value of mortality in patients with acute PE[ 20 ]. For example, Collomb et al[ 21 ] have shown that the hemodynamic severity of acute PE can be determined by assessing clot burden through the use of a vascular obstruction index as well as other vascular load measurements such as right ventricular (RV): left ventricular (LV) ratio, minimum LV diameter and diameter of the central PA[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…61 The location and extent of clot is known to be associated with evidence of heart dysfunction. 62,63 Quantity of clot can be integrated into models to predict right ventricular dysfunction, 64 including those assessing maximal clot size. 65 While these methods are promising, further studies to build consensus on the best method of measuring clot burden are ongoing.…”
Section: Ct Angiography For Diagnosis and Prognosticationmentioning
confidence: 99%